Aortic arch origin of the left vertebral artery: An Anatomical and Radiological Study with Significance for Avoiding Complications with Anterior Approaches to the Cervical Spine. Issue 6 (12th June 2017) - Tardieu, Gabrielle G.; Edwards, Bryan; Alonso, Fernando; Watanabe, koichi; Saga, Tsuyoshi; Nakamura, Moriyoshi; Motomura, Mayuko; Sampath, Raghuram; Iwanaga, Joe; Goren, Oded; Monteith, Stephen; Oskouian, Rod J.; et al.
Abstract : Complications from anterior approaches to the cervical spine are uncommon with normal anatomy. However, variant anatomy might predispose one to an increased incidence of injury during such procedures. We hypothesized that left vertebral arteries that arise from the aortic arch instead of the subclavian artery might take a more medial path in their ascent making them more susceptible to iatrogenic injury. Fifty human adult cadavers were examined for left vertebral arteries having an aortic arch origin and these were dissected along their entire cervical course. Additionally, two radiological databases of CTA and arteriography procedures were retrospectively examined for cases of aberrant left vertebral artery origin from the aortic arch over a two‐year period. Two cadaveric specimens (4%) were found to have a left vertebral artery arising from the aortic arch. The retrospective radiological database analysis identified 13 cases (0.87%) of left vertebral artery origin from the aortic arch. Of all cases, vertebral arteries that arose from the aortic arch were much more likely to not only have a more medial course (especially their preforaminal segment) over the cervical vertebral bodies but also to enter a transverse foramen that was more cranially located than the normal C6 entrance of the vertebral artery. Spine surgeons who approach the anterior cervical spine should be aware that an aortic origin of the left vertebral artery is likely to be closer to the midline and less protected above the C6 vertebral level. Clin. Anat. 30:811–816, 2017. © 2017Wiley Periodicals, Inc.